2014
DOI: 10.4236/jbise.2014.79072
|View full text |Cite
|
Sign up to set email alerts
|

Non-Linear EEG Measures in Meditation

Abstract: In this study, the performance of Sevcik's algorithm that calculates the fractal dimension and permutation entropy as discriminants to detect calming and insight meditation in electroencephalographic (EEG) signals was assessed. The proposed methods were applied to EEG recordings from meditators practicing insight meditation and calming meditation before as well as during both types of meditation. Analysis was conducted using statistical hypothesis testing to determine the validity of the proposed meditation-id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 19 publications
2
27
1
Order By: Relevance
“…The patterns of changes observed using MF, IAF, SampEn and LZC parameters did not necessarily imply that Snoezelen ® 15 therapy produces neural repair in participants. However, we hypothesize that the changes described in this study are related with higher levels of psychophysiological relaxation of the participants, since similar EEG alterations have been described during different relaxation strategies [35][36][37][38][39][40][41]. Nevertheless, other results (e.g.…”
Section: Discussioncontrasting
confidence: 44%
See 2 more Smart Citations
“…The patterns of changes observed using MF, IAF, SampEn and LZC parameters did not necessarily imply that Snoezelen ® 15 therapy produces neural repair in participants. However, we hypothesize that the changes described in this study are related with higher levels of psychophysiological relaxation of the participants, since similar EEG alterations have been described during different relaxation strategies [35][36][37][38][39][40][41]. Nevertheless, other results (e.g.…”
Section: Discussioncontrasting
confidence: 44%
“…When compared to rest, meditation seems to be accompanied by a complexity decrease, maybe due to the disconnection of irrelevant brain networks for the maintenance of focused internalized attention and inhibition of inappropriate information [39]. In a recent study, a statistically significant reduction in the permutation entropy was found after insight meditation and calming meditation [41]. Natarajan et al [40] demonstrated that EEG is characterized by a less complex and 16 more regular behavior after music and reflexological stimulation, which completely agrees with our SampEn and LZC results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonlinear statistics, such as Lyapunov stability theory and stochastic analysis (Wang et al, 2018), and nonlinear interdependence to reflect dynamical systems complexity (Lo et al, 2018), are being embraced to investigate the poly-dimensionality and nonlinearity of meditation EEG-substrates. Fractal dimension/FD (the degree of chaos within the brain's time series) and permutation entropy (the degree of uncertainty within a random variable, such as EEG signal) may provide statistical sensitivity to detect meditation-associated neural correlates, since increased FD (network complexity) has been observed in experienced Vipassana meditators (Kakumanu et al, 2018), and "focused breath" vs. "open monitoring" meditation, significantly so for the former (Vyšata et al, 2014). Moreover, permutation entropy may have utility in gauging meditation stability, since reduced PE related to either meditative-state and/or proficiency was reported in both studies.…”
Section: Electrophysiological Trajectories: Mathematical Multi-dimensmentioning
confidence: 99%
“…There has been a great deal of research works focusing on detecting the attention and relaxation (meditation) states of mind from the characteristics of EEG ( Aftanas & Golocheikine, 2001 ; Jacobs & Friedman, 2004 ; Lin & John, 2006 ; Hamadicharef et al, 2009 ; Rebolledo-Mendez et al, 2009 ; Jiang et al, 2011 ; Li et al, 2011 ; Liu, Chiang & Chu, 2013 ; Patsis et al, 2013 ; Vyšata et al, 2014 ; Kaur & Singh, 2015 ). The detection of the attention and meditation is important in many fields, including clinical studies of stress reduction, sleep deprivation, fatigue, educational studies of learner attention and game studies of player concentration and engagement.…”
Section: Introductionmentioning
confidence: 99%